THE INFLUENCE OF CORPORATE GOVERNANCE MECHANISMS ON CARBON EMISSION DISCLOSURE: DOES GREEN PERFORMANCE MATTER? - Lina, Lina; Devyanti, Catarine (JRAK, 2024)
Carbon emissions disclosure has attracted researchers' attention. This study aims to provide empirical evidence on the influence of more comprehensive corporate governance mechanisms on carbon emission disclosure based on legitimacy and stakeholder theories. This study introduces virtue ethics theory, a new theory in carbon emission research, to explain the moderating role of green performance. Observational data includes 455 data from a sample of companies listed on the Indonesia Stock Exchange from 2018 to 2022. The research data was processed using multiple linear regression methods and moderated regression analysis. The study's results prove that the size of the board of commissioners, the independence of the board of commissioners, the sustainability committee, and institutional ownership positively affect carbon emission disclosure. The green performance also revealed can strengthen the influence of board of commissioners diversity on carbon emission disclosure. Corporate governance is needed to encourage companies to disclose their carbon emissions.